A closed-form ergodic capacity expression for a generic cooperative diversity network in Rayleigh fading channels - Lee, Min; Oh, Seong Keun (Journal of Communications and Networks, 2019)
In this paper, we derive a closed-form ergodic capacity expression for a generic cooperative diversity network (GCDN) in Rayleigh fading channels. We first derive a closed-form probability density function (pdf) of the instantaneous diversity-combined signal-to-noise ratio, and then a closed-form ergodic capacity expression for the GCDN by using the derived closed-form pdf. Through numerical analyses, we analyze the ergodic capacities according to the number of cooperative nodes (CNs), respective numbers of CN antennas, and respective channel qualities between a set of the CNs and a user terminal, and also characterize the resulting ergodic capacity behaviors.
Keywords: Channel quality; Closed form; CoMP; Cooperative diversity networks; Diversity transmission; Ergodic capacity; Probability density function (pdf); User terminals; CoMP; cooperative diversity network; ergodic capacity; joint diversity transmission